2007
DOI: 10.1158/1078-0432.ccr-06-0691
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Clinical-Genomics Approach Identifies a Candidate Multi-Analyte Blood Test for Serous Ovarian Carcinoma

Abstract: Purpose: Cancer of the ovary confers the worst prognosis among women with gynecologic malignancies, underscoring the need to develop new biomarkers for detection of early disease, particularly those that can be readily monitored in the blood. Experimental Design: We developed an algorithm to identify secreted proteins encoded among f22,500 genes on commercial oligonucleotide arrays and applied it to gene expression profiles of 67 stage I to IV serous papillary carcinomas and 9 crudely enriched normal ovarian t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The diagnostic significance of CA 125 is well recognized in patients with EOC [4,5,7,8]. Serum MMP-7 was previously reported to be increased in patients with EOC compared to healthy controls; however, it was noticed that such study was limited CA 125, MMP-7 and CCL18 were significantly increased in patients with benign ovarian lesions compared to controls (P \ 0.001, P \ 0.001, P = 0.002, respectively) CCL11 was significantly decreased in ovarian cancer patients compared to either controls (P = 0.010) or patients with benign ovarian lesions (P = 0.037) * P value is significant to serous ovarian carcinoma [29]. MMP-7 can promote cancer invasion by proteolytic cleavage of the ECM substrates [14].…”
Section: Discussionmentioning
confidence: 92%
“…The diagnostic significance of CA 125 is well recognized in patients with EOC [4,5,7,8]. Serum MMP-7 was previously reported to be increased in patients with EOC compared to healthy controls; however, it was noticed that such study was limited CA 125, MMP-7 and CCL18 were significantly increased in patients with benign ovarian lesions compared to controls (P \ 0.001, P \ 0.001, P = 0.002, respectively) CCL11 was significantly decreased in ovarian cancer patients compared to either controls (P = 0.010) or patients with benign ovarian lesions (P = 0.037) * P value is significant to serous ovarian carcinoma [29]. MMP-7 can promote cancer invasion by proteolytic cleavage of the ECM substrates [14].…”
Section: Discussionmentioning
confidence: 92%
“…In addition to proteins that have been assayed in the blood as potential ovarian cancer biomarkers, we investigated proteins that were recently described as potential markers by Kulasingam et al (21) based on their proteomic identification in ovarian cancer cell lines (6, 22), ascites (23, 24), and tumor tissue (25), and oligonucleotide microarray experiments (26). Table 2 presents proteins that were identified in at least 3 of 6 ovarian cancer proteomic and/or transcriptomic studies for which data for the effects of HRT on their levels was available.…”
Section: Resultsmentioning
confidence: 99%
“…In LMP tumors and well-differentiated OCs, RAS mutations are frequently observed, whereas only a few such mutations have been found in G2/3 OCs (Shih and Kurman 2004;Dehari et al 2007). Our group (Meinhold-Heerlein et al 2007) recently demonstrated by gene expression profiling that LMP/G1 differentiated OCs clustered together and G2/ 3 OCs shared similarities in gene expression profiles. On the contrary, p53 has been shown to be frequently mutated in moderately and poorly differentiated OC (Salani et al 2008).…”
Section: Discussionmentioning
confidence: 93%